Penggunaan Sensor Kelembaban Tanah untuk Penetapan Jadwal Penyiraman Tanaman Cabai melalui Irigasi Tetes: Use of Soil Moisture Sensors to Determine Chili Irrigation Scheduling through Drip Irrigation - Susila, Anas D; Ketty Suketi; Mathias Pratama (Jurnal Hortikultura Indonesia (JHI), 2023)
Fertigation through drip irrigation is an adaptation technology in dealing with climate change. Chili planting using drip irrigation in dry land requires an appropriate watering schedule. The aim of this study was to evaluate the watering method based on soil moisture sensors and evapotranspiration values in chili planting using drip irrigation. The research was conducted at the Cikarawang Experimental Field, IPB University, Bogor, from July to September 2022. Imola chili varieties were grown on fields with available P content of 19.6 ppm (medium) and available K of 84.64 ppm (high) (Mechlih-1), 1.45 % C Organic, and a pH of 6.85. Treatment of the watering schedule of the arrangement in a randomized block design with 1xETc, 2xETc (without sensor), 2xETc-S (using a soil moisture sensor) treatment with 6 repetitions. The results showed that all watering methods could be used to support chili production with an average productivity of 8,825 - 10,797 ton ha-1. In general, the 2xETc-S treatment produced the highest fruit weight per bed compared to the 1xETc and 2xETc treatments. The highest unmarketable pasar chili fruit weight per bed was in the 2xETc treatment. For commercial field implementation, it is necessary to consider the number of sensors, humidity thresholds, and watering volume to maximize quality and productivity. Keywords: dryland, evapotranspiration, irrigation scheduling, soil moisture sensor